Chiral ligand‐induced photoluminescence intermittence difference of CdTe quantum dots. (19th July 2018) - Yang, Jie; Dong, Chaoqing; Ren, Jicun
Abstract: Semiconductor quantum dots (QDs) are a new nano‐material, and their unique optical properties have become a focal point of research in both academia and industry. In this study, we studied photoluminescence (PL) intermittence (or 'blinking') behaviors of individual QDs prepared with different chiral ligands by using single molecule microscopy and single molecule fluorescence correlation spectroscopy (FCS). We found that the chirality of N ‐isobutyryl‐d /l ‐cysteine (D/L‐NIC) as surface stabilizers significantly influences PL blinking behaviors of cadmium telluride (CdTe) QDs synthesized in aqueous solution. The 'on time' distribution and the power‐law exponent analyses show that the D‐NIC more efficiently suppresses the blinking of QDs over L‐NIC. Ensemble spectroscopies verfied that the remarkably‐different blinking behaviors of QDs induced by ligand chirality were attributed to the different number of chiral ligands bound in the surface of QDs.